Cross‐Coupling through Ag(I)/Ag(III) Redox Manifold. Issue 62 (8th October 2021) - Demonti, Luca; Saffon‐Merceron, Nathalie; Mézailles, Nicolas; Nebra, Noel
Abstract: In ample variety of transformations, the presence of silver as an additive or co‐catalyst is believed to be innocuous for the efficiency of the operating metal catalyst. Even though Ag additives are required often as coupling partners, oxidants or halide scavengers, its role as a catalytically competent species is widely neglected in cross‐coupling reactions. Most likely, this is due to the erroneously assumed incapacity of Ag to undergo 2 e − redox steps. Definite proof is herein provided for the required elementary steps to accomplish the oxidative trifluoromethylation of arenes through Ag I /Ag III redox catalysis (i. e. CEL coupling), namely: i ) easy Ag I /Ag III 2 e − oxidation mediated by air; ii ) bpy/phen ligation to Ag III ; iii ) boron‐to‐Ag III aryl transfer; and iv ) ulterior reductive elimination of benzotrifluorides from an [aryl‐Ag III ‐CF3 ] fragment. More precisely, an ultimate entry and full characterization of organosilver(III) compounds [K] + [Ag III (CF3 )4 ] − (K‐1 ), [(bpy)Ag III (CF3 )3 ] (2 ) and [(phen)Ag III (CF3 )3 ] (3 ), is described. The utility of 3 in cross‐coupling has been showcased unambiguously, and a large variety of arylboron compounds was trifluoromethylated via [Ag III (aryl)(CF3 )3 ] − intermediates. This work breaks with old stereotypes and misconceptions regarding the inability of Ag to undergo cross‐coupling by itself. Abstract : Teaching silver to do the trick . Most crucial steps towards oxidative trifluoromethylation via Ag I /Ag III redox shuttles are herein deciphered. This innovative cross‐coupling, analogous to the CEL coupling popularized by copper, involves: i) easy Ag I /Ag III 2 e − oxidation; ii) phen ligation to Ag III ; iii) boron‐to‐Ag III aryl transfer; and iv) benzotrifluoride production from aryl‐Ag III intermediates. Now, Ag III CF3 chemistry is safe and reachable from AgF, KF, CF3 TMS and air.